Fault tolerant tracking controller design for T-S fuzzy disturbed systems with uncertainties subject to actuator faults - Aouaouda, S.; Tarek, K. M.; Bouarar, T.; Ichalal, D.; Chadli, M. (ETFA2011, 2011)
The investigated fault tolerant control (FTC) problem for uncertain nonlinear systems with external disturbances against actuator faults is addressed. The aim is to synthesize a fault tolerant controller ensuring trajectory tracking for a class of nonlinear systems represented by Takagi-Sugeno (T-S) models with measurable premise variables. In order to design the FTC law a proportional integral observer (PIO) is adopted which estimate both of the faults and the faulty system states. Based on Lyapunov theory, and L 2 optimization, the trajectory tracking performance and the stability of the closed loop system are analyzed. Sufficient conditions are obtained in terms of linear matrix inequalities (LMI). Simulation results show the effectiveness of the proposed method.